Carbon Credits and Compliance: Assessing Indonesia’s Progress on Article 6.2 Implementation (2019–2023) - Danuwijaya, Try; Ongom, Trevor Graham (JOSH: Journal of Sharia, 2025)
Indonesia is positioning itself as a key actor in international carbon markets under Article 6.2 of the Paris Agreement, which enables the transfer of carbon credits through Internationally Transferred Mitigation Outcomes (ITMOs). This study employs a mixed-methods approach, combining policy analysis with emissions data from 2019 to 2023, to evaluate Indonesia’s readiness and progress in implementing Article 6.2. During this period, Indonesia’s greenhouse gas (GHG) emissions averaged 1,117.82 MtCO₂e, peaking at 1,200.20 MtCO₂e in 2023 well below the 2030 unconditional cap of 1,954.76 MtCO₂e and significantly lower than the Business-as-Usual (BAU) projection of 2,869 MtCO₂e. Despite this, a linear upward trend in annual emissions was observed, indicating that emissions are gradually increasing over time and may approach the target cap if not addressed. While policy frameworks such as Presidential Decree No. 98/2021 provide foundational support, Indonesia still faces technical and institutional capacity gaps. The findings suggest that although current emissions remain within target levels, the rising trend underscores the urgency for more robust and accelerated mitigation efforts to ensure long-term compliance with climate commitments.